Bіoethics and relіgion: theoretical and methodological problems of the study - Шавріна, I. В. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
The paper analyzes the problems common to bioethics and religion. Particular attention is paid to the choice of moral rights being secularand religious in nature. One of the main problems of bioethics – the formation of bioethical outlook is discussed. It is associated withthe moral choice, moral responsibility and moral human right. The author analyzes the relevance of religious research for bioethics as anew science of civilized society.